Methodological plot: thoretical narratives for a permanent “A/R/TograForm” in art/education (Revista Apotheke, 2024)
This article presents a methodological plot of theoretical narratives for a permanent “A/R/TograFormar” in art/education, that is, theories that supported the development of permanent training for art/educators in Basic Education in Uberlândia /MG. The training actions were carried out in the “Art/education Training Workshop”, the locus of the intervention action linked to the action research being developed in the doctoral thesis in progress in the Postgraduate Program in Education at the Federal University of Triângulo Mineiro – UFTM, under the title “A/R/TograFormar: dialogues between art/education, creation process and permanent teacher training”. As a trainer and Workshop leader, we promote practical actions, readings and theoretical/imaginative studies of art, anchored in the theoretical-practical issues of art research, and in the methodological perspectives of the medium as point zero, of triangular approach, from a/r/tography, interventional action research and in active methodologies that culminated in the creation of “Imagetic Narratives”. The methodological framework contributed to the teacher, artist, researcher and trainer (proponent) finding methodological paths for an “A/R/tograFormar” in the permanent training process for active art teachers/educators.
Keywords: art/education; on going training; methodologies in art; imagery narratives